A new frog of the genus Pristimantis (Amphibia: Strabomantidae) from the high Andes of Southeastern Ecuador, discovered using morphological and molecular data - Arteaga-Navarro, Alejandro F.; Guayasamin, Juan M. (Zootaxa, 2011)
We describe a new small sized (SVL in females ≤ 25.7 mm; in males, ≤ 20.1 mm) Pristimantis, associated with bamboodominated forests in the Reserva Mazar, Andes of Southeastern Ecuador, at elevations between 2876–2989 m. This species is assigned to the P. orestes group, from whose members it differs by the absence of tubercles on heel and outer edge of tarsus, lacking a discoidal fold, presence of slightly expanded finger and toe pads, and bright yellow blotches on groin, axilla and anterior surfaces of thigh. The advertisement call of the new species consists of a series of short, indistinctly pulsed notes, and has a dominant frequency of 2.50–2.56 kHz. A molecular phylogeny based on a fragment of the mitochondrial gene 12S shows that the new species is sister to a clade formed by Pristimantis simonbolivari and an undescribed Pristimantis.